Strategi Pemasaran Dan Pengelolaan Keuangan Pada Program "Bank Sayur" Hidroponik Rumah Tangga Berbasis Ekonomi Berkelanjutan - Agus Wicahyono; Muhammad Fiqi Hidayatulloh; Maulida Kurniawati; Kristanti Kristanti; Desi Fitri Indriyani (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2026)
Access to fresh and healthy vegetables in urban areas remains limited due to dependence on external supplies, leading to high costs and reduced product freshness. The Community Service Program (PkM) “Vegetable Bank” serves as a solution to empower households to produce small-scale, pesticide-free hydroponic vegetables, while simultaneously strengthening household economies through a collective marketing system. This activity was carried out in Gedog Wetan Village, Turen Subdistrict, Malang Regency, in June 2025, involving community health workers (Kader), youth organizations (Karang Taruna), and village officials as target partners.The implementation consisted of five main stages: survey and socialization, technical training, cultivation assistance, marketing simulation and financial recording, and final evaluation. The methods employed included hydroponic training, application of the marketing mix (4Ps), and training in basic financial recording. As a result, participants were able to produce high-quality vegetables, market their products both locally and online, and independently prepare financial reports. This program not only improved family skills and income, but also created a community-based local food resilience model that can be replicated